Channeled Autonomy: The Joint Effects of Autonomy and Feedback on Team Performance Through Organizational Goal Clarity. (November 2016) - Gonzalez-Mulé, Erik; Courtright, Stephen H.; DeGeest, David; Seong, Jee-Young; Hong, Doo-Seung
Past research suggests that autonomy has highly variable effects on team performance, and that one explanation for this pattern of findings is that autonomous teams fall into a state of disorder where they lack clarity regarding the goals of the broader organization. Following this perspective, the authors develop a model proposing that performance feedback coupled with high autonomy enables teams to have greater clarity of the organization's goals, which in turn increases team performance. This model was tested on 110 teams in a defense industry manufacturing firm in South Korea using mediated-moderation techniques. Results indicate that highly autonomous teams that receive a high degree of performance feedback outperform other teams because of their heightened level of organizational goal clarity. In contrast, highly autonomous teams that receive low levels of feedback perform at the lowest levels compared to other teams because of a lack of organizational goal clarity. The authors discuss the implications of these findings for theory, research, and practice.